A comparative study on ITS (intelligent transport system) standardization policies in the U.S. and Europe - Run Duan (Heliyon, 2023)
Standardization is an essential link in the process of moving a technological system from research and development to application. As more international standards shift from “post-standard” to “pre-standard”, policies are playing an increasingly significant role in the process of standardization. In this study, we sorted out the ITS (Intelligent Transport System) standardization policy in the United States and Europe in chronological order from 1991 to 2012, comparing the context of policy documents and extracting four dimensions to discuss the influence of policy on technical standardization, which are the policy priorities, the role of government, policy intervention time, and cooperation. The results show that policy priorities and government roles influence each other and influence intervention time and cooperation. Policy priorities driven by infrastructure construction and the leadership role of the government have made the government more actively involved in the standardization process at an early stage and promoted top-down cooperation. Policy priorities driven by strengthening technological competitiveness and a supportive government role have had the opposite effect. Policy intervention time and cooperation have a direct impact on technology research and development, standardization, and integration. The results also confirm the importance of policies that strengthen the development of common technologies and mobilize stakeholder participation, as well as actively facilitate the transformation of domestic standards into international ones, providing insight for latercomers.